Investigations on the Fusants From Wide Cross Between White-Rot Fungi and Saccharomyces cerevisiae Reveal Unknown Lignin Degradation Mechanism - Shao, Qi; Li, Xin; Chen, Ying; Zhang, Zhijun; Cui, Yong; Fan, Huan; Wei, Dongsheng (Frontiers in Microbiology, 2022)
Degradation of lignocellulose by fungi, especially white rot fungi, contributes a lot to carbon cycle, bio-fuel production and many other bio-based applications. However, the existing enzymatic and non-enzymatic degradation mechanisms cannot be unequivocally supported by in vitro simulation experiment, meaning that additional mechanisms might exist. Right now, it is still very difficult to discover new mechanisms with traditional forward genetic approaches. To disclose novel lignin degradation mechanisms in white rot fungi, a series of fusants from wide cross by protoplast fusion between Pleurotus ostreatus, a well-known lignin degrading fungus and S. cerevisiae, a well-known model organism unable to degrade lignocellulose, was investigated regarding their abilities to degrade lignin. By analyzing the activity of traditional lignin degrading enzyme, the ability to utilize pure lignin compounds and degrade corn stalk, a fusant D1-P was screen out and proved not to contain well recognized lignin degrading enzyme genes by whole genome sequencing. Further investigation with two-dimension Nuclear Magnetic Resonance (NMR) showed that D1-P was found to still be able to degrade the main lignin structure β-O-4 linkage, leading to reduced level of this structure similar to that of the wild type strain P. ostreatus after a 30-day semi-solid fermentation. It was also found that D1-P showed a degradation preference to β-O-4 linkage in Aβ(S)-threo. Therefore, wide cross between white rot fungi and S. cerevisiae provides a powerful tool to uncover novel lignocellulose degradation mechanism that will contribute to green utilization of lignocellulose to produce bio-fuel and related bio-based refinery.